Productivity of corn grown in the crop rotation and as monoculture under long-term fertilizing - A. F. Stulin (Зерновое хозяйство России, 2018)
Productivity of corn grown in the crop rotation and as monoculture under long-term fertilizing In 1971-2015 on the Voronezh leached black earth there were conducted the researches of the effect of long-term use of various kinds, doses, combinations of fertilizers in the 10 crop rotation sequences and in corn-corn monoculture on its productivity. It has been determined that the yearly N60Р60К60 fertilizing increased the productivity of green chop, dry matter and corn grain on 8.8, 2.53 and 1.29 t/ha in crop rotation and on 10.1, 2.71 and 1.32 t/ha in monoculture in comparison with the productivity of green chop, dry matter and corn grain without fertilizing (26.2, 6.42 and 3.42 t/ha in crop rotation; 22.1, 5.65 and 2.81 t/ha in monoculture). Due to the crop rotation the increase of green chop, dry matter and corn grain productivity was 2.4-4.1; 0.3-0.8 and 0.5-0.6 t/ha respectively. The largest content of organic carbon was estimated in the topsoil. The archive soil sample contained 3.19% of carbon; in black fallow (since 1960) it was 3.12%; in corn-corn monoculture without fertilizing it was 3.37% and with the yearly N60Р60К60 fertilizing it was 3.42%. In the soil layer of 60-80 cm there were no significant differences in the amount of organic carbon.